Torque Controlled Drive for Permanent Magnet Direct Current Brushless Motors - Britten, Mark David (Department of Electrical Engineering, 2014)
This thesis describes the design and implementation of a simple variable speed drive (VSD) based on a brushless direct current (BLDC) machine and discrete logic circuits. A practical VSD was built, capable of operating a BLDC machine in two quadrants, motoring and regenerative braking. The intended applications are electric scooters and electric bicycles, where the recovered energy from braking extends the range of the vehicle. A conceptual four quadrant VSD, suitable for three and four wheelers requiring reverse operation, was designed and tested in simulation. Simplicity was emphasized in this design to help achieve a robust, easy to analyse system. The versatility of multi-function gate integrated circuits (ICs) made them ideal for implementing the commutation logic and keeping the system simple. The BLDC machine has sensors with a resolution of 60 ed to determine rotor position. An electronic commutator or phase switcher module interprets the position signals and produces a switching pattern. This effectively transforms the BLDC machine into a direct current (DC) brushed machine. A synchronous step down converter controls the BLDC machine current with a tolerance band scheme. This module treats the BLDC machine as if it was a DC machine. The leakage inductance of the electric machine is used as the inductive filter element. The unipolar switching scheme used ensures that current flows out of the battery only for motoring operation and into the battery only during regeneration. The current and torque are directly related in a DC brushed machine. The action of an electronic commutator or phase switcher creates that same relationship between torque and current in a BLDC machine. Torque control is achieved in the BLDC machine using a single channel current controller. The phase switcher current is monitored and used to control the duty ratio of the synchronous converter switches. Successful operation of the practical VSD was achieved in two quadrants: forwards motoring and forwards regenerating. The maximum tested power outputs were 236W in motoring mode and 158W in regenerating mode. The output torque could be smoothly controlled from a positive to a negative value. iv v Simulation of the conceptual four quadrant design was successful in all the motoring, generating and active braking zones. The required manipulation of logic signals to achieve this type of operation was done automatically while the machine was running. The resulting output torque is smoothly controlled in all of the operating zones. Commutation at certain speeds and torques are handled better by some topologies than others. Some current sensing strategies adversely affect instantaneous phase currents under certain conditions. The final design chose the method where phase currents experience no overshoot, minimizing component stress. The battery, or energy storage system, used in verifying the operation of the VSD in the practical electric bicycle was found to be the most limiting component. In regenerating mode, the low charge acceptance rate of the battery reduced the maximum retarding torque and energy recovery rate.